2019
DOI: 10.3390/ijms20225610
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structural Model of Human MALAT1 Reveals Multiple Structure–Function Relationships

Abstract: Human metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is an abundant nuclear-localized long noncoding RNA (lncRNA) that has significant roles in cancer. While the interacting partners and evolutionary sequence conservation of MALAT1 have been examined, much of the structure of MALAT1 is unknown. Here, we propose a hypothetical secondary structural model for 8425 nucleotides of human MALAT1 using three experimental datasets that probed RNA structures in vitro and in various human cell lines. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 79 publications
2
70
0
Order By: Relevance
“…PAN lncRNA folds into three branched domains and its 5 Mta responsive element (MRE) region and 3 expression and nuclear retention element (ENE) are identified in a larger structural context. A recent study identified the secondary structure of MALAT1, an important cancer-related lncRNA, in vitro and in various human cell lines [92]. In addition to providing protein/RNA-binding structural information, this study reveals that the structure of lncRNA MALAT1 can be perturbed by RNA modifications, mutations in cancer, and single-nucleotide polymorphisms.…”
Section: Secondary Structure Of Lncrnasmentioning
confidence: 88%
“…PAN lncRNA folds into three branched domains and its 5 Mta responsive element (MRE) region and 3 expression and nuclear retention element (ENE) are identified in a larger structural context. A recent study identified the secondary structure of MALAT1, an important cancer-related lncRNA, in vitro and in various human cell lines [92]. In addition to providing protein/RNA-binding structural information, this study reveals that the structure of lncRNA MALAT1 can be perturbed by RNA modifications, mutations in cancer, and single-nucleotide polymorphisms.…”
Section: Secondary Structure Of Lncrnasmentioning
confidence: 88%
“…39 For example, a change in the secondary structure of MALAT1 disrupted miR-217-5p binding to MALAT1. 40 Pan et al. 10 demonstrated that the c.713A>G/714T>C dinucleotide substitution induces a significant change in the GAS8-AS1 secondary structure, so we speculated that the difference of the secondary structure between the mutant and WT GAS8-AS1 may have caused this result.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, Brown et al demonstrated that the METTL16 binds at the 3′ UTR triple helical region of MALAT1 [ 113 ]. Moreover, m 6 A changes in MALAT1 alter its binding capacity of miRNAs involved in cancer [ 114 ]. RNA-binding motif protein 15 (RBM15) and RMB15B are also part of the METTL3 complex and target the X-inactive specific transcript ( XIST ) lncRNA [ 115 ].…”
Section: Ncrna Chemical Modifications In Cancermentioning
confidence: 99%